The carretilla (smart click trolley) / Nor Sherry Arini Ramli...[et al.] - Ramli, Nor Sherry Arini; Rosman, Nurfatin Shafika; Md Rani, Nurfarahaila Saqira; Mohd Razali, Siti Nor Farini (2019)
The product to be developed is a Smart Click Trolley which is a trolley that suit the convenience of customers provided with wireless function which works automatically to climb the stairs. The trolley is controlled by application that can installed for free in our smart phone. The idea to develop this trolley is invented from a problem in our college. Whenever the lift at our college was out service due to hard rain and thunder, students was having a hard time bringing big stuff such as a box of mineral water to their room. They had to use the stairs to reach to their college level, it is quiet worrying since this also can cause incident to the students while reaching to their floor. Due to this problem, we also imagine that how residence that live in flat or apartment that does not have lift or the lift maybe out of service too, how they want to carry a heavy load to their home such as gas to cook. Therefore, our team took an initiative to innovate a smart, effective and high functionality trolley so that the user can use it to climb the stairs without using much energy.